2007
DOI: 10.1118/1.2777278
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of image acquisition techniques for dual‐energy imaging of the chest

Abstract: Experimental and theoretical studies were conducted to determine optimal acquisition techniques for a prototype dual-energy (DE) chest imaging system. Technique factors investigated included the selection of added x-ray filtration, kVp pair, and the allocation of dose between low- and high-energy projections, with total dose equal to or less than that of a conventional chest radiograph. Optima were computed to maximize lung nodule detectability as characterized by the signal-difference-to-noise ratio (SDNR) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…The system was modified for the purposes of DE imaging to include: 1) a flat-panel detector (Trixell Pixium-4600, Moirans, France) with a ~250 mg/cm 2 CsI:Tl scintillator and 143 µm pixel pitch, 2) a fingertip pulse oximeter to trigger x-ray exposure during diastole for reduction of cardiac motion artifacts, (44) and 3) a multi-position filter wheel within the collimator to change the added filtration between the low-kVp (2.5 mm Al) and high-kVp (2 mm Al + 0.6 mm Ag) exposures, as guided by previous studies of DE image quality performed in our laboratory. (44)(45)(46) The X-ray tube produces a polychromatic beam with spectrum of beam energies distributed around the pre set target tube potential. Therefore, a high-energy filter was selected to "harden" the high energy beam, to reduce spectral overlap between the low-and high-energy projections.…”
Section: De Imaging Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The system was modified for the purposes of DE imaging to include: 1) a flat-panel detector (Trixell Pixium-4600, Moirans, France) with a ~250 mg/cm 2 CsI:Tl scintillator and 143 µm pixel pitch, 2) a fingertip pulse oximeter to trigger x-ray exposure during diastole for reduction of cardiac motion artifacts, (44) and 3) a multi-position filter wheel within the collimator to change the added filtration between the low-kVp (2.5 mm Al) and high-kVp (2 mm Al + 0.6 mm Ag) exposures, as guided by previous studies of DE image quality performed in our laboratory. (44)(45)(46) The X-ray tube produces a polychromatic beam with spectrum of beam energies distributed around the pre set target tube potential. Therefore, a high-energy filter was selected to "harden" the high energy beam, to reduce spectral overlap between the low-and high-energy projections.…”
Section: De Imaging Systemmentioning
confidence: 99%
“…This was the subject of considerable investigation in our laboratory (45,46,47). Differential filtration between low-and high-kVp projections was selected and an extensive analysis of contrast, Noise Equivalent Quanta (NEQ) and nodule detectability for low-and high -kVp added filtration was performed.…”
Section: De Imaging Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies [17][18][19] have suggested the CNR is maximized with ~30% flux allocation, defined as the percentage of entrance skin exposure of the low-kVp to that of the low-and highkVp combined. That is, roughly speaking, the exposure ratio between the low-and high-kVp is …”
Section: Fluxmentioning
confidence: 99%
“…The monitor recorded pulse oximetry and x-ray trigger signals to determine whether a given x-ray exposure was delivered synchronous to diastole or systole. Previous studies identified the optimal imaging techniques: 29 an LE beam at 60 kVp and an HE beam at 120 kVp ͑0.6 mm Ag+ 2 mm Al added filtration͒, with the radiation dose allocated such that approximately 1 / 3 of the total energy was imparted by the LE beam, and with total dose equivalent to that of a conventional PA chest radiograph ͑e.g., 0.11 mGy for average chest thickness͒.…”
Section: Iib Imaging Systemmentioning
confidence: 99%